Ramat Raḥel VI the renewed excavations by the Tel Aviv-Heidelberg expedition (2005-2010) : the Babylonian-Persian pit - Lipshits, ʿOded 1963-; Froid, Liʾorah 1955-; Oeming, Manfred 1955-; Gadot, Yuval 1967- (Penn State University Press, 2021)
This is part of a three-volume final report of the renewed excavations at Ramat Raḥel by the Tel Aviv-Heidelberg Expedition (2005−2010). It presents the finds from the Babylonian-Persian pit, one of the most dramatic find-spots at Ramat Raḥel. The pit yielded a rich assemblage of pottery vessels and yhwd, lion, and sixth-century "private" stamp impressions, including, for the first time, complete restored stamped jars, jars bearing two handles stamped with different yhwd impressions, and jars bearing both lion and "private" stamp impressions on their bodies. Residue analysis was conducted on many of the vessels excavated from the pit to analyze their contents, yielding surprising results. The finds contribute to our understanding of the pottery of the Babylonian and early Persian periods (6th−5th centuries BCE) and to the study of the development of the stamped-jar administration in the province of Yehud under Babylonian and Persian rule.Also available from Eisenbrauns: Ramat Raḥel III: Final Publication of Aharoni''s Excavations at Ramat Raḥel (1954, 1959-1962) by Oded Lipschits, Yuval Gadot, and Liora Freud; and Ramat Raḥel IV: The Renewed Excavations by the Tel Aviv-Heidelberg Expedition (2005-2010): Stratigraphy and Architecture, by Oded Lipschits, Mandred Oeming, and Yuval Gadot
Keywords: SOCIAL SCIENCE / Archaeology; Excavations (Archaeology) -- Israel -- Ramat Raḥel